THE RELATION BETWEEN PROPERTY RIGHTS, DIGITAL PIRACY AND CONSUMER BEHAVIOR - RADU CEZARA-GEORGIANA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2024)
This study examines the factors influencing consumers' decisions to opt for pirated products within the digital realm. It provides a definition of digital piracy and elucidates its adverse impact on the parties implicated. Additionally, the research highlights the challenge of addressing and combating this infringement of intellectual property rights in the digital environment, emphasizing the widespread acceptance of such practices and its consequential financial repercussions for affected companies due to people's inactivity.